Identifikasi Anisakis sp. pada Cumi-cumi (Loligo spp.) di Pasar Wuring dan TPI Kota Maumere - Deran Ola, Elisa Albertine Rahmita; Almet, Julianty; Detha, Annytha Inna Rohi (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
Maumere City is one of the largest squid producers in NTT with a total production and catch of 143,958 tons. Squid has various health benefits, but squid is also susceptible to parasitic infections such as Anisakis sp.. Anisakis sp. is an anisakid nematode that can cause anisakiasis, which is zoonotic and dangerous to humans. This study aims to determine the type and calculate the prevalence of Anisakis sp. on squid (Loligo spp.) traded at Pasar Wuring and TPI Maumere City. The collection used the sampling quota method with a total sample of 100 squids divided into 5o samples at Wuring Market and 50 samples at TPI Maumere City. The sample was then necropsy to look for the presence of Anisakis sp. on internal organs of the body. The parasite was found collected in a Petri dish containing NaCl, then fixed with 70% alcohol, stained with Semichon’s acetocarmine, then dehydrated and stratified with 70% alcohol, 85% 95%. Next, identify it under a microscope. The results showed that the type of parasite that infects squid is Anisakis sp. type I, characterized by clear boring teeth, ventriculus, and mucron. The prevalence of Anisakis sp. in squid is 11% which belongs to the category of frequent predilection organs on the muscular wall of the anterior mantle, liver, and muscular wall of the caudal coat.